PROXIMATE AND FUEL PROPERTIES OF AFRICAN LOCUST BEAN PULP AND CASSAVA STARCH FLOUR BINDERS FOR FUEL BRIQUETTE PRODUCTION - Namadi, Surajo; Musa, A. O.; Gana, U. M.; Safana, A. A.; Sani, J. (FUDMA Journal of Sciences, 2024)
The study investigates the proximate and combustion properties of affordable and locally available briquette binders, namely: African locust bean pulp and cassava starch (flour) using the American Society for Testing and Materials (ASTM) methods. The findings indicate varying levels of moisture content (4.55% to 6.89%), volatile matter (30.06% to 64.21%), ash content (0.93% to 23.36%), and fixed carbon (7.89% to 62.12%). Elemental composition of carbon, hydrogen, and oxygen range from 34.24% to 53.25%, 4.39% to 5.09%, and 32.96% to 33.19%, respectively. The calorific values obtained in the study are 16.85±0.48 MJ/kg for African locust bean pulp and 20.69±0.34 MJ/kg for cassava starch flour. Both binders exhibit properties conducive to producing high-quality briquettes capable of generating sufficient heat for household and small-scale industrial settings.
Keywords: African Locust bean pulp; Briquette; Cassava Starch flour; Proximate Analysis; Calorific value